Analysis of the electrocardiogram in face of the change in the position of the electrodes: controlled clinical trial (Research, Society and Development, 2022)
Objective: To analyze the electrocardiographic record in the face of intervention in the placement of electrodes on the chest compared to the standard method. Method: Controlled clinical trial, single blind, conducted with 41 patients, who composed the control and intervention groups, generating records that were lauded by two health professionals, proficient in cardiology. Results: Eighty-two electrocardiograms were analyzed, guided by the control and intervention protocols, which included the description of correct and incorrect techniques, respectively. Most of the variables studied did not present a statistically significant difference regarding the reports analyzed when comparing the protocols applied. The exception was the P wave, which was negative in V1 when it should have been positive, as evidenced in the comparison between 14 pairs of electrocardiograms (P = 0.003). Conclusion: The incorrect positioning of the electrodes affected the recording of lead V1. Considering the twelve-lead electrocardiogram usually performed in clinical practice, the possible confusion due to the underlying anatomical landmarks of other procedures, such as, for example, the focus of cardiac auscultation, is highlighted. We suggest the development of additional and technological criteria for the recognition and detection of lead location errors, as well as professional training being a sine qua non condition for carrying out the electrocardiography exam. (ReBEC - NCT: RBR-9h4tp3).